Two remarkable new species of Hypothenemus Westwood (Curculionidae: Scolytinae) from Southeastern USA - Johnson, Andrew J.; Atkinson, Thomas H.; Hulcr, Jiri (Zootaxa, 2016)
Two new Hypothenemus species found in southern and southeastern USA are described: Hypothenemus piaparolinae sp. n. and Hypothenemus subterrestris sp. n. The distribution and habits suggest these species are native and widely distributed, but elusive, and not recently arrived exotics. Both appear to have unusual biology: H. subterrestris appears to live in material on or in the ground, and H. piaparolinae has only been collected from the xylem of extensively rotten, fungus-filled twigs.